Lack of Causal Effects or Genetic Correlation between Restless Legs Syndrome and Parkinson's Disease. Issue 8 (11th May 2021) - Estiar, Mehrdad A.; Senkevich, Konstantin; Yu, Eric; Varghaei, Parizad; Krohn, Lynne; Bandres‐Ciga, Sara; Noyce, Alastair J.; Rouleau, Guy A.; Gan‐Or, Ziv
ABSTRACT: Background: Epidemiological studies have reported an association between Parkinson's disease (PD) and restless legs syndrome. Objectives: We aimed to use genetic data to study whether these 2 disorders are causally linked or share genetic architecture. Methods: We performed two‐sample Mendelian randomization and linkage disequilibrium score regression using summary statistics from recent genome‐wide meta‐analyses of PD and restless legs syndrome. Results: We found no evidence for a causal relationship between restless legs syndrome (as the exposure) and PD (as the outcome, inverse variance‐weighted; b = −0.003, SE = 0.031, P  = 0.916; F statistic = 217.5). Reverse Mendelian randomization also did not demonstrate any causal effect of PD on restless legs syndrome (inverse variance‐weighted; b = −0.012, SE = 0.023, P  = 0.592; F statistic = 191.7). Linkage disequilibrium score regression analysis demonstrated lack of genetic correlation between restless legs syndrome and PD (rg = −0.028, SE = 0.042, P  = 0.507). Conclusions: There was no evidence for a causal relationship or genetic correlation between restless legs syndrome and PD. The associations observed in epidemiological studies could be attributed, in part, to confounding or nongenetic determinants. © 2021 International Parkinson and Movement Disorder Society